2022
DOI: 10.1108/pm-11-2021-0086
|View full text |Cite
|
Sign up to set email alerts
|

The use of blended synchronous learning for property education in and beyond the COVID-19 pandemic

Abstract: PurposeThe COVID-19 outbreak has brought serious disruptions worldwide and higher education has been at the forefront of this global pandemic. To adapt to the “new normal”, new technology-backed teaching mode emerges in universities as valued option to integrate face-to-face and remote teaching-learning activities. Blended synchronous learning (BSL) forms part of this new trial. This paper investigates the relevance and implications of BSL for university teaching and learning in the field of property and built… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“… Cheung and Wu (2022) conducted a study on the applicability and implications of Blended Synchronous Learning (BSL) for academic property and built environment teaching and learning during and after the pandemic. The study found that blended learning is a practical and innovative teaching method that can foster a welcoming and fair learning environment, and produce high-quality learning outcomes for property education.…”
Section: Research Themesmentioning
confidence: 99%
See 1 more Smart Citation
“… Cheung and Wu (2022) conducted a study on the applicability and implications of Blended Synchronous Learning (BSL) for academic property and built environment teaching and learning during and after the pandemic. The study found that blended learning is a practical and innovative teaching method that can foster a welcoming and fair learning environment, and produce high-quality learning outcomes for property education.…”
Section: Research Themesmentioning
confidence: 99%
“…Furthermore, the pandemic has created significant obstacles for educational institutions and industries in less developed areas where resources for blended synchronous learning (BSL) are limited, resulting in greater disparities in the allocation of educational resources and competencies. Cheung and Wu (2022) recommended further research using BSL in the design and delivery of specific types of subjects during and after the pandemic. Another suggestion is to compare BSL models across countries and institutions to examine the effects of technological development on teaching and learning in different contexts.…”
Section: Future Map Of Teaching and Learning Modes In Higher Business...mentioning
confidence: 99%
“…The call for nursing as expressions of unending care to education re-structuring brought multiple impressions of challenges and pressures to academic stakeholders. Varied views surfaced due to the existence of digitalization, economic disparity, lessened student-teacher interaction, and inadequate digital infrastructure, which demands emergent action to address the crisis (Menon & Suresh, 2022;Cheung & Wu, 2022;Stanworth, Yen, & Warden, 2022;Zafitsara & Velo, 2022). Some academic institutions in developed countries have already promoted flexible learning (Webb, McQuaid, & Webster, 2021).…”
mentioning
confidence: 99%
“…They suggest that blended learning can provide students with more personalized and adaptive learning experiences, as well as opportunities for self-directed learning and collaboration. From the quantitative perspectives there is also the agreement that BL enhances learning outcomes (Belur et al, 2023;Cheung & Wu, Similar enhanced learning outcomes have been reported in the field of virtual microscopy (Herodotou et al, 2020). The purpose of the study was to unravel the knowledge gap in respect of students' preference and satisfaction with either face-to-face or blended learning for superior learning outcomes.…”
mentioning
confidence: 57%
“…In the field of built and property education, evidence has been found for BL as a critical success factor post-pandemic (Cheung & Wu, 2023;Tahir et al, 2022). Cheung and Wu's (2022) study explores the role of Blended Synchronous Learning (BSL) in property education at the University of Melbourne and evaluates its prospects in view of the challenges brought about by the worldwide epidemic in the context of the institution's effort to adjust to the "new norm" during and after the pandemic.…”
mentioning
confidence: 99%